2021
DOI: 10.1073/pnas.2119258119
|View full text |Cite
|
Sign up to set email alerts
|

THESEUS1 modulates cell wall stiffness and abscisic acid production in Arabidopsis thaliana

Abstract: Plant cells can be distinguished from animal cells by their cell walls and high-turgor pressure. Although changes in turgor and the stiffness of cell walls seem coordinated, we know little about the mechanism responsible for coordination. Evidence has accumulated that plants, like yeast, have a dedicated cell wall integrity maintenance mechanism. It monitors the functional integrity of the wall and maintains integrity through adaptive responses induced by cell wall damage arising during growth, development, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 69 publications
1
54
0
Order By: Relevance
“…In recent years, a mechanism required to monitor CW structure, namely CW integrity (CWI) maintenance, has been described in plants. In this mechanism, several proteins belonging to the CrRLK1L subfamily were described to function as CW sensors ( Bacete et al, 2022 ; Engelsdorf et al, 2018 ; Gigli-Bisceglia et al, 2020 ; Vaahtera et al, 2019 ). In our attempt to understand the role of CrRLK1Ls in regulating salt stress responses, we studied the double herk1 the1-4 mutant, which was originally reported to lack the function of both the CrRLK1Ls THE1 and HERK1, and only later characterized for being a combination of herk1 loss-of-function and the1-4 gain-of-function alleles ( Merz et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, a mechanism required to monitor CW structure, namely CW integrity (CWI) maintenance, has been described in plants. In this mechanism, several proteins belonging to the CrRLK1L subfamily were described to function as CW sensors ( Bacete et al, 2022 ; Engelsdorf et al, 2018 ; Gigli-Bisceglia et al, 2020 ; Vaahtera et al, 2019 ). In our attempt to understand the role of CrRLK1Ls in regulating salt stress responses, we studied the double herk1 the1-4 mutant, which was originally reported to lack the function of both the CrRLK1Ls THE1 and HERK1, and only later characterized for being a combination of herk1 loss-of-function and the1-4 gain-of-function alleles ( Merz et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that PM-localized CrRLK1Ls (such as THE1, HERK1 and FER) regulate similar metabolic and cellular responses. For example, it has recently been reported that THE1, similarly to FER, functions as negative regulator of ABA synthesis in response to osmotic stress ( Bacete et al, 2022 ; Zhao et al, 2021 ). Whether HERK1 together with THE1 would affect ABA metabolism and/or synthesis and would contribute to altering salt stress responses remains to be determined, but certain salt-induced FER-dependent phenotypes, such as stunted growth in salt, seem to be abolished upon disruption of ABA biosynthesis or ROS accumulation ( Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, MLG43, and in a lower extend CEL3, have been described to be perceived by cereals suggesting that additional receptors to LRR-MAL RLKs (e.g., LysM-RLKs for MLGs in rice) would be involved in these perception mechanisms (32,33). MLG-and cellulose-derived oligosaccharides can be also released upon alteration of plant cell wall integrity triggered by other stresses (e.g., salt or drought) or during plant development (e.g., cell wall remodelling: (71,72)). During these processes plant endogenous enzymes can hydrolase cell wall polysaccharides, as described recently for a maize GH17 licheninase that releases MLG43 and other oligosaccharides from MLGs (73).…”
Section: Discussionmentioning
confidence: 99%